Exploring the Housing Pathways of Low-Income Women: A Biographical Approach. Issue 1 (2nd January 2016) - Skobba, Kim
Abstract: This research explores the use of a housing pathways framework and a biographical method to improve our understanding of the long-term housing experiences of low-income women. Biographical methods have been employed in the study of vulnerable and special populations outside of the US; however, there has been limited application of the method to examine low-income households within the US. This study draws on interviews of 29 low-income women with children in a large Midwestern metropolitan area to examine the nature of low-income housing pathways. The wages provided in the jobs that were available to the women in this study were insufficient to afford even low-quality, low-rent apartments, suggesting that the ability to achieve stability in modest housing is predicated on achieving much higher levels of household income. Federal rental assistance provided through the Housing Choice Voucher programme, rather than increased job stability or wages, resulted in improved housing conditions and stability for the women in this study. Biographical methods present great potential in providing a nuanced understanding of the housing experiences and life circumstances of low-income households and other vulnerable populations in the United States.